End-to-side Versus end-to-end neurorrhaphy at the peroneal nerve in rats - Viterbo, Fausto [UNESP]; Brock, Ryane Schmidt; Maciel, Fábio; Ayestaray, Benoit; Garbino, José Antonio; Rodrigues, Cecília Pessoa [UNESP] (FapUNIFESP (SciELO), 2017)
Purpose: To evaluate three different kinds of neurorrhaphy of the peroneal nerve. Methods: Eigthy rats were divided into 5 groups. Control: nerve had no intervention. End-toend (EE): nerve was cut and elongated with a nerve graft with two end-to-end neurorrhaphies. End-to-side (ES): nerve was cut and sutured to the graft with at the lateral side of the nerve. Side-to-end (SE): the nerve was cut and sutured to the graft with end-to-end neurorrhaphy. Denervated: nerve was cut and both endings were buried into the muscle. The evaluation was done by walking track analysis, electrophysiology, body mass, cranial tibial muscle mass, nerve and muscle fibers morphometry. Results: The EE, ES and SE have the same potential of reinnervation. Conclusion: There is no functional or histological difference between these different types of neurorrhaphy.
Keywords: Microsurgery; Nerve regeneration; Peripheral nerves; Peroneal nerve; Rats